Effects of Whole Body Vibration on Muscle Strength and Quality of Life in Health Elderly: A Meta-Analysis - Maíra Florentino Pessoa; Daniella Cunha Brandão; Rafaela Barros de Sá; Helga Cecília Muniz de Souza; Helen Kerlen Bastos Fuzari; Armele Dornelas de Andrade
Abstract Introduction: The literature presents different findings about the vibration training efficacy on muscle per- formance, even using protocols with similar parameters. Objective: The purpose of this systematic review was to investigate the effects of whole body vibration (WBV) on strength and quality of life in health elderly people, presenting a meta-analisys. Methods: PubMed, CINAHL, SciELO, LILACS and PEDro databases were systematically searched for studies that used WBV in healthy elderly. These searches were supplemented with material identified in references and a qualitative and quantitative analysis was performed to sum- marize the findings. The search was performed by two independent researchers with a third was selected to solve problems of search disagreement, data collection, and quality score. Results: Nine studies with strength outcome and two studies with quality of life outcome were identified, with sample ranging 21 to 220 elderly, all studies had control groups performing exercises or guidelines. Some studies have shown sig- nificant improvements in muscle strength, muscle power, vertical jump height, timed get up and go test and quality of life. Conclusion: The meta-analysis of the findings in these studies shows that WBV could benefit health elderly, increasing muscle strength and improving the quality of life mainly in functional capacity. The number of publications found in the databanks searched is small, with limitations in design of protocols with a weakness to the interpretation of the findings, suggesting the need of investigation with WBV with well-designed protocols and controlled parameters into the effects of WBV training in elderly people.